Ophiostomatoid fungi synergize attraction of the Eurasian spruce bark beetle, Ips typographus to its aggregation pheromone in field traps - Jirošová, Anna; Modlinger, Roman; Hradecký, Jaromír; Ramakrishnan, Rajarajan; Beránková, Kateřina; Kandasamy, Dineshkumar (Frontiers in Microbiology, 2022)
Eurasian spruce bark beetle, Ips typographus is a destructive pest of the Norway spruce (Picea abies). Recent outbreaks in Europe have been attributed to global warming and other anthropogenic impacts. Bark beetles are guided by multiple complex olfactory cues throughout their life cycle. Male-produced aggregation pheromones, comprising 2-methyl-3-buten-2-ol and cis-verbenol, have been identified as the most powerful attractants for dispersing conspecifics. In addition to host trees, bark beetles interact with multiple organisms, including symbiotic ophiostomatoid fungi, which may promote beetle colonization success and offspring development. Previously, in a short-distance laboratory assay, we demonstrated that I. typographus adults are attracted to the volatile organic compounds (VOCs) produced by three symbiotic fungi: Grosmannia penicillata, Endoconidiophora polonica, and Leptographium europhioides. Furthermore, the abundant fusel alcohols and their acetates were found to be the most attractive odorants in the fungal VOC profile. In this study, using a long-distance field-trapping experiment, we analyzed the role of fungal VOCs as attractants for dispersing I. typographus. Two types of fungal lures were tested in combination with pheromones in traps: (1) live cultures of fungi grown on potato dextrose agar (PDA) and (2) dispensers containing synthetic fusel alcohols and their acetates in equal proportions. Subsequently, the composition of VOCs emitted from live fungal lures were analyzed. We found that the symbiotic fungi synergistically increased the attraction of beetles to pheromones in field traps and the attractiveness of live fungal lures depended on the fungal load. While one Petri dish with E. polonica, when combined with pheromones synergistically increased trapping efficiency, three Petri dishes with L. europhioides were required to achieve the same. The synthetic mix of fungal fusel alcohols and acetates improved the catch efficiency of pheromones only at a low tested dose. VOC analysis of fungal cultures revealed that all the three fungi produced fusel alcohols and acetates but in variable composition and amounts. Collectively, the results of this study show that, in addition to pheromones, bark beetles might also use volatile cues from their symbiotic fungi to improve tree colonization and reproductive success in their breeding and feeding sites.